Harnessing T cells to fight cancer with BiTE® antibody constructs – past developments and future directions. Issue 1 (March 2016) - Klinger, Matthias; Benjamin, Jonathan; Kischel, Roman; Stienen, Sabine; Zugmaier, Gerhard
Summary: Bispecific T‐cell engager (BiTE ® ) antibody constructs represent a novel immunotherapy that bridges cytotoxic T cells to tumor cells, thereby inducing target cell‐dependent polyclonal T‐cell activation and proliferation, and leading to apoptosis of bound tumor cells. Anti‐CD19 BiTE ® blinatumomab has demonstrated clinical activity in Philadelphia chromosome (Ph)‐negative relapsed or refractory (r/r) acute lymphoblastic leukemia (ALL) eventually resulting in conditional approval by the U.S. Food and Drug Administration in 2014. This drug is currently further developed in pediatric and Ph + r/r, as well as in minimal residual disease‐positive ALL, and might also offer clinical benefit for patients with non‐Hodgkin's lymphoma, especially for those with aggressive forms like diffuse large B‐cell lymphoma. Another BiTE ® antibody construct in hemato‐oncology designated AMG 330 targets CD33 on acute myeloid leukemia blast cells. After showing promising ex vivo activity, this drug candidate has recently entered phase 1 clinical development, and has further indicated potential for combination with checkpoint inhibitors. In solid tumor indications, three BiTE ® antibody constructs have been tested in phase 1 studies so far: anti‐EpCAM BiTE ® AMG 110, anti‐CEA BiTE ® MEDI‐565/AMG 211, and anti‐PSMA BiTE ® BAY2010112/AMG 212. Pertinent questions comprise how to maximize BiTE ® penetration and T‐cell infiltration of the tumor while simultaneously minimizing any adverse events, which is currently explored by a continuous intravenous infusion approach. Thus, BiTE ® antibody constructs will hopefully provide new treatment options for patients in several indications with high unmet medical need.